THE ANALYSIS OF VILLAGE FUND CONTRIBUTION TO ACHIEVE A NATIONAL SUSTAINABLE DEVELOPMENT GOAL (SDGs VILLAGE) IN GADINGREJO VILLAGE, KEPIL SUBDISTRICT WONOSOBO REGENCY - Ahmad Subekti (International Journal of Social Science, 2022)
One of the goals of the Village Fund disbursement is to be able to contribute to accelerating the achievement of sustainable national development goals (SDGs Desa). However, in reality, the allocation of the Village Fund which has entered its eighth year carried out by the village government often does not consider sustainable development factors. stated that for villages in Indonesia, the localization of SDGs into Village SDGs was really needed. In fact, the Village SDGs are the main reference for the medium-term development of villages throughout Indonesia. The proven SDGs make it easier to measure development. The measure itself is comprehensive on aspects of people's lives and their environment. Therefore, the localization of SDGs as Village SDGs makes the direction of village development clear and detailed in holistic goals, namely the real contribution of using Village Funds to accelerate the achievement of sustainable national development goals. By using qualitative methods (Cresswel, 2015), this study examines how the problem of the contribution of the Village Fund in sustainable development in Gadingrejo Village, Kepil District, Wonosobo Regency. This study will use the approach proposed by A. Halim Iskandar (2020) regarding the Village SDGs to Accelerate the Achievement of Sustainable National Development Goals. The research findings describe six dimensions, namely (1) Prosperous Villagers (2) Natural balance (3) Village prosperity (4) Peace (5) Partnership and (6) Village Institutions and Wisdom. The contribution of village funds in Gadingrejo Village to finance and maximize the six dimensions mentioned above has not been fully achieved.